2011
DOI: 10.1589/jpts.23.707
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selective-task vs Set-task Program on Balance and Weight Bearing of Stroke Patient

Abstract: Abstract. [Purpose] This study investigated the change in functional balance and weight bearing of stroke patients in a set-task balance training program and a selective-task balance training program.[Method] the participants were randomly allocated to either the set-task program or the selective-task program. We evaluated balance capacity using the Berg Balance Scale (BBS). Postural weight bearing was measured using a Tetrax Intractive Balance System, and the lower extremity function was evaluated using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…Steadiness is defined as the ability to maintain a stable standing position with minimal movement (10,11). The result of this study about the COP path length and COP area was similar to some previous studies that evaluated postural sway in patients with stroke (1,5,12,31). For example, Tsaklis et al (10) examined the effects of learning weight transfer on balance and weight distribution in 9 male patients with chronic stroke after 4 weeks.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Steadiness is defined as the ability to maintain a stable standing position with minimal movement (10,11). The result of this study about the COP path length and COP area was similar to some previous studies that evaluated postural sway in patients with stroke (1,5,12,31). For example, Tsaklis et al (10) examined the effects of learning weight transfer on balance and weight distribution in 9 male patients with chronic stroke after 4 weeks.…”
Section: Discussionsupporting
confidence: 78%
“…Sudden loss of neurological function in a stroke due to interruption of blood supply to the brain can lead to disability in adults (1). Approximately 90% of patients who have survived following a stroke have difficulties in motor control and balance functions (2,3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bayouk 19 ) reported significant improvements in 10-m walking and balance (p<0.05) in chronic stroke patients who participated in an 8-week task-oriented training program, including sensory inputs. Ahn 20 ) reported that task-oriented training for chronic stroke patients increased BBS scores significantly, from 30.5±2.3 to 32.9.±1.7. Nichols 21 ) reported that balancing function was associated with ADL, such as walking, getting dressed, and movement, and that balancing function was necessary for the successful performance of these activities 22 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In another study Ahn et al examined 30 patients which were randomly allocated to experimental and control group. In this study patients also showed significant improvement in BBS scores after the application of task-selective program [ 43 ]. In contrast to this, in another study conducted by Salbach et al no improvement was observed in BBS scores of chronic stroke patients given a task specific walking exercises for the period of 6 weeks [ 44 ].…”
Section: Discussionmentioning
confidence: 91%